Health in Uruguay: Progress and Challenges in the Right to Health Care Three Years after the First Progressive Government - Fernando Borgia (Social Medicine Publication Group, 2008)
Using a social medicine perspective, this article describes the Frente Amplio [Broad Front] government strategies for creating a more social, productive, democratic, innovative, and culturally integrated Uruguay. This nation will recognize health as a basic human right, is concerned about the general well being of its population, and understands the need for public health reform. The present health reform is at the heart of Uruguay's current social, economic and political transformations, changes which have a moral-ethical and social justice dimension. The health proposal calls for substantive transformation, requiring three parallel progressive changes: in health care delivery, in health care management and in health care financing. The current reform has created a mixed private-public Integrated National Health Care System and an increasingly well funded National Health Insurance program. The process is new and evolving, transcendent, democratic, and participatory. Keywords: social medicine, right to health, human rights, reform, Integrated National Health Care System.